UPAYA PENINGKATAN HAFALAN AL-QURAN PELAJAR SMP N 04 AIR PURA, NAGARI TLUK KUALO INDERAPURA, KEC. AIR PURA, KAB. PESISIR SELATAN - Harahap, Samsul Bahry; Syamsarina, Syamsarina (Institut Agama Islam Negeri Kerinci, 2023)
One of the areas on the South Coast of West Sumatra is Nagari Tluk Kualo Inderapura, Kec. Temple Water. This village consists of 2 villages, namely Rimbo Lumang Village and Medan Baik Village. In Rimbo Lumang Village there are 2 public schools, namely SD N 09 Air Pura and SMP N 04 Air Pura. One of the extra-curricular programs is the Tahfidz activity, namely training to memorize Al-Quran Juz 30. The aim of this activity is to increase students' enthusiasm for memorizing the Al-Quran and help students memorize the Al-Quran more easily. This activity uses the method of reading 10 verses and repeating them 10 times and also uses the Cinta Quran Apk for reading. This method is quite effective for students, however due to the lack of students who can read the Al-Quran fluently and students who can already read the Al-Quran fluently have other activities that are mixed up, this makes this program not run well. So very few students take part in the Tahfidz program. But this tahfidz program can be said to be successful as an effort to improve the memorization of the Al-Quran for students at SMP N 04 Air Pura for those who take part.